Learning to drive [videorecording (DVD)] - Clarkson, Patricia; Kingsley, Ben, 1943-; Weber, Jake, 1964-; Gummer, Grace, 1986-; Pollitt, Katha (Broad Green Pictures, 2016)
A feel-good, coming of (middle) age comedy about a mismatched pair who helps each other overcome life's road blocks.